PENGOLAHAN LIMBAH CAIR LABORATORIUM DENGAN BERBAGAI WAKTU RETENSI - Siti Rhofiah; Bambang Joko Priatmadi; Taufiqur Rohman; M. Adriani (Universitas Lambung Mangkurat, 2011)
According to the Indonesian Government Regulation Number 85 Year 1999 about the processing of B3 waste, the laboratorys waste water classified to B3 (Bahan Berbahaya Beracun). Based on this, then conducted laboratory research on wastewater treatment using chemical processes, biology and physics with a variation of time are 5 hours, 10 hours and 15 hours. Test parameters studied were Iron (Fe) and Mangan (Mn). The Goal of this study was to determine the effectiveness of the decrease in the concentration of iron (Fe) and Mangan (Mn) using a combination of processing by the processing chemistry, biology and physics with a variation of residence time is 5 hours, 10 hours and 15 hours. Based on initial test data, the initial concentration is known to Iron (Fe) is 46.4 mg / l while the initial concentrations of manganese (Mn) is 3,91 mg / l, where the concentration exceeds the ambien. From the results revealed that the decrease in Fe content of the most effective outcome of the time of 15 hours is able to reduce up to 99,78% Fe with a concentration of 0,1 mg / l, while the decrease in Mn content of the most effective results on the time of 15 hours, able to reduce up to 86,70% Mn with a concentration of 0,52 mg / l.